2007
DOI: 10.1161/01.hyp.0000255233.56410.20
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Oxidative Stress-Induced Increase in Salt Sensitivity and Development of Hypertension in Sprague-Dawley Rats

Abstract: Abstract-High salt intake produces vascular changes that contribute to the development of hypertension in salt-sensitive individuals. Because reactive oxygen species play a role in the pathogenesis of cardiovascular diseases, we investigated whether oxidative stress contributes to salt-sensitive hypertension. Sprague-Dawley rats were divided in different groups and received tap water (vehicle), 30 mmol/L of L-buthionine sulfoximine ([BSO] an oxidant), high salt ([HS] 1% NaCl), and BSO plus HS without and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 49 publications
4
46
0
1
Order By: Relevance
“…However, Tempol significantly reduced both oxidative stress and blood pressure, but it failed to completely normalize the BSO effects, probably because of its inability to normalize glutathione levels, in BSO-treated rats. 31 Nevertheless, these data confirm previous findings that oxidative stress could be an independent risk factor to the development of hypertension by exaggerating AT 1 R expression, response, and stimulation of renal sodium transporters. 1,30,[32][33][34] Ang II via AT 1 Rs activates serine/threonine and tyrosine kinase pathways, both of which can regulate NHE3 activity.…”
Section: Discussionsupporting
confidence: 88%
“…However, Tempol significantly reduced both oxidative stress and blood pressure, but it failed to completely normalize the BSO effects, probably because of its inability to normalize glutathione levels, in BSO-treated rats. 31 Nevertheless, these data confirm previous findings that oxidative stress could be an independent risk factor to the development of hypertension by exaggerating AT 1 R expression, response, and stimulation of renal sodium transporters. 1,30,[32][33][34] Ang II via AT 1 Rs activates serine/threonine and tyrosine kinase pathways, both of which can regulate NHE3 activity.…”
Section: Discussionsupporting
confidence: 88%
“…Studies from our laboratory also showed that, during oxidative stress, HS intake attenuated the vasodepressor responses to endothelialdependent and -independent vasoactive compounds despite NO synthase upregulation. 46 Taken together, these data show that the increased salt sensitivity in conditions associated with oxidative stress may be contributed by both renal and extrarenal signaling molecules responsible for sodium homeostasis and vascular tone.…”
Section: Oxidative Stress Hs Intake and Bpmentioning
confidence: 74%
“…A positive relationship between oxidative stress and blood pressure were demonstrated in some models of experimental hypertension. 42 For example, an upregulation of reactive oxygen species appeared to precede the development of hypertension, 43,44 and an antioxidant regimen arrested the process. 44,45 In vasculature, the major source of reactive oxygen species was from a family of non-phagocytic NAD(P)H oxidases, which comprised a catalytic core (Nox/p22 phox ) and several cytosolic subunits (p47 phox , p67 phox , p40 phox , Rac).…”
Section: Molecular Targets Of Chlorogenic Acid In Blood-pressure Regumentioning
confidence: 99%